COX-2 inhibition decreases VEGF expression and alveolar bone loss during the progression of experimental periodontitis in rats - Oliveira, Thais M.; Sakai, Vivien T.; Machado, Maria Aparecida A. M.; Dionisio, Thiago J.; Cestari, Tania Mary; Taga, Rumio; Amaral, Sandra L. [UNESP]; Santos, Carlos F. (Amer Acad Periodontology, 2008)
Background: Vascular endothelial growth factor (VEGF) is a macromolecule of importance in inflammation that has been implicated in periodontitis. The aims of this study were to investigate VEGF expression during the progression of periodontal disease and to evaluate the effect of a preferential cyclooxygenase (COX)-2 inhibitor meloxicam on VEGF expression and alveolar bone loss in experimentally induced periodontitis.Methods: A total of 120 Wistar rats were randomly separated into groups 1 (control) and 2 (meloxicam, 3 mg/kg/day, intraperitoneally, for 3, 7, 14, or 30 days). Silk ligatures were placed at the gingival margin level of the lower right first molar of all rats. VEGF expression was assessed by reverse transcription-polymerase chain reaction (RT-PCR), Western blot (WB), and immunohistochemical (IHC) analyses. The hemiarcades were processed for histopathologic analysis. RT-PCR and WB results were submitted to analysis of variance, the Tukey test, and Pearson correlation analysis (P<0.05).Results: A reduction in alveolar bone resorption was observed in the meloxicam-treated group compared to the control group at all periods studied. There was a positive correlation between COX-2 mRNA and VEGF mRNA in the gingival tissues and periodontal disease (R = 0.80; P = 0.026). Meloxicam significantly reduced the increased mRNA VEGF expression in diseased tissues after 14 days of treatment (P = 0.023). Some alterations in VEGF receptor I mRNA expression were observed, but these were not statistically significant. VEGF protein expression in WB experiments was significantly higher in diseased sites compared to healthy sites (P<0.05). After 14 days of treatment with meloxicam, an important decrease in VEGF protein expression was detected in diseased tissues (P = 0.08). Qualitative IHC analysis revealed that VEGF protein expression was higher in diseased tissues and decreased in tissues from rats treated with meloxicam.Conclusions: The present data suggest an important role for VEGF in the progression of periodontal disease. Systemic therapy with meloxicam can modify the progression of experimentally induced periodontitis in rats by reducing VEGF expression and alveolar bone loss.
Keywords: alveolar bone loss; cyclooxygenase-2; inflammation; meloxicam; periodontal disease; vascular endothelial growth factor